Short-Term Consolidation of Information for Episodic Memory: The Role of Attention. - ÖZÇELİK, Erol; TEKMAN, Hasan Gürkan (Journal of Faculty of Letters / Edebiyat Fakultesi Dergisi)
Pieces of evidence from rapid serial visual presentation, attentional blink, and dual-task interference phenomena propose that human beings have a significant limitation on the short-term consolidation process. Short-term consolidation is transferring perceptual representations to a more durable form of memory. Although previous research has shown that masks presented after targets interrupt the consolidation process of information, there is not enough evidence for the role of attention in consolidation for episodic memory. Three experiments were conducted to investigate the effects of attention and stimulus onset asynchrony (SOA) between targets and masks on episodic memory. Masks were presented after targets with varying SOAs. The participants in the divided attention condition performed the attention-demanding secondary task after the presentation of the masks, whereas participants in the full attention condition were not requested to perform the secondary task after the presentation of masks. The results showed that reducing SOA between targets and masks caused an impairment in memory performance for divided attention but not for full attention, providing evidence for the necessity of attention for the short-term consolidation process.